2018
DOI: 10.3390/insects9030092
|View full text |Cite
|
Sign up to set email alerts
|

The Rolling of Food by Dung Beetles Affects the Oviposition of Competing Flies

Abstract: Flies are the main competitors of dung beetles for oviposition sites and rolling dung beetles relocate their food to reduce interspecific competition. Furthermore, dung beetles deposit chemical substances on the food ball that may repel fly larvae and certain predators. In the present study, using Deltochilum furcatum, a dung beetle that does not exhibit parental care and the blow-fly, Lucilia cuprina, we tested the hypothesis that pygidial secretions deposited on the food ball could also make it less attracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Each dung beetle species likely affected the survival of coprophilic flies additively by damaging fly eggs and larvae inside the dung, especially during the brood ball formation (Braga et al, 2012;Ix-Balam et al, 2018). Such a complementarity mechanism is also prompted by increased FEve between species (Hillebrand et al, 2008), as shown by our model in which fly larvae abundance was negatively correlated with the FEve of dung beetle assemblages.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Each dung beetle species likely affected the survival of coprophilic flies additively by damaging fly eggs and larvae inside the dung, especially during the brood ball formation (Braga et al, 2012;Ix-Balam et al, 2018). Such a complementarity mechanism is also prompted by increased FEve between species (Hillebrand et al, 2008), as shown by our model in which fly larvae abundance was negatively correlated with the FEve of dung beetle assemblages.…”
Section: Discussionmentioning
confidence: 59%
“…In agreement with our initial hypothesis, a niche complementarity mechanism governs the interaction between dung beetles and coprophilic flies, as the abundance of fly larvae in unburied dung pats was negatively correlated with the species richness of dung beetles. Each dung beetle species likely affected the survival of coprophilic flies additively by damaging fly eggs and larvae inside the dung, especially during the brood ball formation (Braga et al, 2012; Ix‐Balam et al, 2018). Such a complementarity mechanism is also prompted by increased FEve between species (Hillebrand et al, 2008), as shown by our model in which fly larvae abundance was negatively correlated with the FEve of dung beetle assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…Allomones are another multifunctional chemical found in dung beetles, related to defense, aggression, and protection of the food resource and the nest. This behavior has been explored in C. cyanellus, C. femoralis and Deltochilum furcatum Laporte (Halffter and Edmonds, 1982;Bellés and Favila, 1983;Favila, 2001;Cortez et al, 2012Cortez et al, , 2015Favila et al, 2012;Ix-Balam et al, 2018). An example of the above is the secretion of the pygidial glands of C. cyanellus, which produce chemicals that act as a defensive substance against Camponotus sericeiventris Guérin-Méneville (Cortez et al, 2012).…”
Section: Chemical Communication At the Reproductive Stage: Semiochemi...mentioning
confidence: 99%
“…It is suggested that pygidial secretions can reduce the oviposition of Lucilia cuprina Wiedemann flies on food balls rolled by beetles. However, whether this is due to the effect of secretions on microbial activity or an allomone effect is unknown (Ix-Balam et al, 2018).…”
Section: Chemical Communication At the Reproductive Stage: Semiochemi...mentioning
confidence: 99%
“…Tibial spur number varies among the species which helps taxonomist to classify the dung beetles (Linz et al, 2019). In addition, head of the dung beetles has a hard, scoop like structure which helps in rolling the dung balls for their nesting (Ix-Balam et al, 2018). Onthophagus taurus (Schreber), as a tunneler makes "multimedia galleries" (tunnels) deep into the soil for laying eggs in the brood balls.…”
mentioning
confidence: 99%